Structure and Mechanical Properties of a Zr-1Nb Alloy, Obtained by the Method of Severe Plastic Deformation; Materials Today: Proceedings; Vol. 2, iss. 1 : ANM2014: 5th International conference on Advanced Nanomaterials - Stepanova E. N. Ekaterina Nikolaevna; Grabovskaya G. P. Galina Petrovna; Mishin I. P. Ivan Petrovich; Bulynko I. P. Dmitry Yurjevich (2015, 2015)
Title screen